2011
DOI: 10.1111/j.1600-0404.2011.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

LINGO1 variants in essential tremor and Parkinson’s disease

Abstract: The leucine-rich repeat and Ig domain containing 1 gene (LINGO1), recently considered to be conferred increased risk of essential tremor (ET), has been also implicated in Parkinson disease (PD). As the two common movement disorders have overlapping clinical and pathological features, it has been postulated that the LINGO1 gene may play a role in the pathogenesis of the two diseases. Here, we review published reports of the LINGO1 variants in ET and PD in an attempt to better understand the molecular and pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
0
28
1
Order By: Relevance
“…Given these overlapping features and the association of LINGO 1 with ET, VillarinoGuell et al [14] investigated the role of LINGO1 in PD and their results revealed an association between LINGO1 and risk of PD. Although these results are not confirmed by other reports, further studies of larger populations are required to investigate the role of LINGO1 in PD [18]. From the pathophysiological perspective, traditionally ET is considered as a primary electrical/elctrophysiological entitiy.…”
contrasting
confidence: 50%
“…Given these overlapping features and the association of LINGO 1 with ET, VillarinoGuell et al [14] investigated the role of LINGO1 in PD and their results revealed an association between LINGO1 and risk of PD. Although these results are not confirmed by other reports, further studies of larger populations are required to investigate the role of LINGO1 in PD [18]. From the pathophysiological perspective, traditionally ET is considered as a primary electrical/elctrophysiological entitiy.…”
contrasting
confidence: 50%
“…36 Various association studies have also shown the role of LINGO1 variants with essential tremor and Parkinson's disease. 37 Moreover, inhibitory anti-LINGO1 antibodies promoted illegitimate oligodendrocyte differentiation and myelination of neurons by inhibiting the function of LINGO1. A similar outcome was observed in the Lingo1 knockout mice and zebrafish lingo1b knockdown models, which revealed early improvement in neuronal myelination as compared to wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, genome-wide association studies of LINGO-1 and LINGO2 variations in PD have generally produced negative results, arguing against a role of LINGO1 variations as a contributing factor in the development of PD [for a recent review, see Deng et al ( 2012 )]. However, genome-wide association studies of LINGO1 and -2 variations have revealed an association with essential tremor, a progressive neurological disorder characterized by symmetric postural or kinetic tremor of the hands and forearms [see Deng et al ( 2012 ), Stefansson et al ( 2009 ), Zeuner andDeuschl ( 2012 ) and Vilarino-Guell et al ( 2010 )].…”
Section: Diseasesmentioning
confidence: 99%
“…However, genome-wide association studies of LINGO1 and -2 variations have revealed an association with essential tremor, a progressive neurological disorder characterized by symmetric postural or kinetic tremor of the hands and forearms [see Deng et al ( 2012 ), Stefansson et al ( 2009 ), Zeuner andDeuschl ( 2012 ) and Vilarino-Guell et al ( 2010 )]. …”
Section: Diseasesmentioning
confidence: 99%